Building up national capability for regional planning and development - Honjo, Masahiko (Philippine Journal of Public Administration, 1976)
This conference paper advances a broad definition of planning and development as one integrated continuing process, planning as both science and art, and regional planning as "the linkage between planning at the national level and reality at the grass roots." It reviews the problems faced by developing countries in regional planning and development and describes the training approach adopted by UNCRD to assist these countries in building up planning capability. In this regard, UNCRD makes the following recommendations: technical assistance and cooperation among the countries concerned must be developed, a trained planning staff must be effectively mobilized, the training curriculum must be revised, and a new type of planning expert able to synthesize planning conditions in an interdisciplinary manner must emerge.